Movement of Tabligh Jama'at Dakwah in Makassar City - Alwi, Izzul Islam; Amin, Muliaty; Arifuddin, Arifuddin (Jurnal Mercusuar, 2021)
This research is titled "The Dakwah Movement of the Majelis Tabligh Muhammadiyah in Makassar City" which examines the Dakwah Movement of the Majelis Tabligh, the obstacles and efforts made by the Muhammadiyah organization in developing dakwah Amar Ma'ruf Nahi Mungkar in Makassar City. It aims to motivate the people of Makassar City to understand the importance of deeper knowledge of true Islam in accordance with the Qur'an and the Sunnah of Prophet Muhammad. The goal is for the people of Makassar City to not only know Islam as a religion only accepted by Allah, but also how Islam can provide a sense of peace, tranquility, mutual respect among society, and obtain happiness in both the world and the hereafter.